THE EFFECT OF EDUCATION AND COMPENSATION ON THE PERFORMANCE OF MEDICOM ACADEMIC LECTURERS AND COMPUTERS - BENA GINTING; Dinaria br Sembiring Sembiring (Jurnal Mantik, 2021)
ABSTRACT This study was conducted to determine the influence of Education and Compensation To the performance of lecturers at the Medicom Computer and Informatics Academy. This study uses two variables consisting of the dependent variable is Performance lecturers (Y), while the independent variable is the Education (X1) and Compensation (X2). This type of research is explanatory research through associative research, the research aims to clarify the relationship between two or more variables. The population in this study were all lecturers  of the  Medicom Computer and Informatics Academy amounted to 35. Methods of data collection is done by questionnaire and literature study. Data analysis was carried out with test data quality (reliability and validity), klasik assumption test, t test (partial test), F test (simultaneous test). The results of the t test show that (1) education has a positive and significant effect on lecturer performance with a t value of 5.676; (2) compensation has a positive and significant effect on the performance of lecturers with a t value of 5.396 (3) The results of hypothesis testing show that education and compensation simultaneously have a positive and significant effect on the performance of lecturers at the Medicom Academy of Informatics and Computers. The results of this study showed that: the impact of Education and Compensation To the performance of lecturers at the Medicom Computer and Informatics Academy positive correlation coefficient (R) = 0.691 and the coefficient of determination (Adjusted Rsquare) of = 0.478 This means that the Performance lecturers (Y) at the Medicom Computer and Informatics Academy amounted to 47.8% influenced by the Education (X1) and Compensation (X2) together.